Design of flexible filter bank in transmultiplexer - Li, Yuchen (2018)
This report mainly studies the basic principles of multi-rate signal processing, presents a method of multi-rate signal flow graphs (MSFGs) and discusses the different ways of channelization. Then, a flexible and efficient structure of non-maximally decimated filter bank (NMDFB) based on oversampling in the channel model is obtained by using polyphase structure and MSFGs. The correctness of this NMDFB is verified by computer simulation